Break-Even Point Analysis and Sales Planning for Financial Strategy Optimization - Azra, Afifah; Azzuhri, Misbahuddin (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – The objectives of this research are to analyze a break-even point and to design earnings plan and sales plan for more effective sales and production.   Design/methodology/approach – The object of this quantitative case study is ASA, a school uniform and ready-to-wear clothing manufacturing company located in Payakumbuh City of West Sumatra. The data was harvested via observations, interviews, and document studies and was processed using time-series analysis, trend analysis, and BEP analysis.  Findings – This study finds that ASA was successful in selling above its break-point in 2018, 2019, 2022, and 2023. The company could meet its earnings plan and sales plan in 2022 and 2023. Originality/value – The practical implementation of this study is that the company's management must always consider and analyze its break-even point to make sure that the business strategies it applies remain relevant with its financial objectives. The company is also suggested to run anticipative plans in case the occurrence of abnormal conditions in order to ensure its sustainability and stability.